Students Marriage Readiness Based on Cultural Background - Elfira, Ninil (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2018)
This study is an attempt to describe the cultural factors in marital readiness. Marital readiness is an important point in creating happiness in domestic life. This research tries to reveal the marital readiness of student based on cultural background. The study was conducted by using the scale of marital readiness instrument, on 57 students with Minangkabau cultural background and Malay culture with data analysis using one way Anova. The results of the analysis illustrate that there are significant differences in marital readiness between students with Minangkabau cultural background and Malay culture. Where minangkabau superior to Malay culture. So that the need for training or intervention to be able to develop the marital readiness.